PENGARUH SUPLEMENTASI HIDROLISAT BULU AYAM DAN MINERAL ORGANIK UNTUK MENINGKATKAN KECERNAAN BAHAN KERING DAN KECERNAAN BAHAN ORGANIK PADA RANSUM SAPI - Kurniawan, Rezza; ., Liman; Widodo, Yusuf (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This research aimed to study the effect level of supplementation of hydrolyzed feather and mineralorganic on cattle. The experiment was applied in latin square design with three treatment and threereplication. The treatments which consisted a: R0= basal ration, R1=basal ration +3% hydrolyzedfeather, R2=R1+ macro organic minerals (Ca-organic 0,5%, Mg-organic 0,04) and micro mineralsorganic (Zn-organic 40 ppm, Cu-organic 10 ppm, Se-organic 0,10 ppm and Cr-organic 0,30 ppm).Analysis of variance, and countinues with least significant different test at level (P>0,05). The resultshowed that hydrolyzed feather and combination of mineral organic, the data where had no effectingto digestibility of dry matter and organic matter on cattle.